A New Design and Application of Bioelastomers for Better Control of Intraocular Pressure in a Glaucoma Drainage Device. Issue 2 (9th July 2013) - Luong, Quang Minh; Shang, Lei; Ang, Marcus; Kong, Jen Fong; Peng, Yan; Wong, Tina T.; Venkatraman, Subbu S.
Abstract Glaucoma drainage device (GDD) implantation is an effective method of lowering the intraocular pressure (IOP). Commonly used GDDs can be classified into nonvalved and valved. Although a stable IOP is critical, currently available devices often cause extreme IOP fluctuations: nonvalved GDDs suffer from a risk of hypotony (IOP < 5 mmHg), whereas valved GDDs have a higher risk ocular hypertensive (IOP > 22 mmHg). It is hypothesized that a GDD with a valve designed to open around the time of onset of the hypertensive phase, would minimize IOP fluctuation. Accordingly, a valve fabricated from a biodegradable polymer poly(L ‐lactide‐co ‐ϵ‐caprolactone) (PLC 70/30) is evaluated in vitro and in vivo. The pressure response is compared with its non‐degradable counterpart in in vitro studies of IOP. It is also established that in vitro, the biodegradability of the valve is programmed to occur over 12 weeks. In vivo, a steady and low IOP is achieved with the biodegradable valve and the hypertensive phase is significantly attenuated compared with the commercial device. Fibrotic encapsulation of the device is also minimized with the biodegradable valve in vivo.